2018
DOI: 10.1080/15230430.2018.1438347
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological changes in Norway spruce deadwood during the early stage of decomposition as a function of exposure in an alpine setting

Abstract: Alpine ecosystems are vulnerable to ever-changing environmental conditions, leading to shifts in vegetation distribution and composition with implications on soil functionality and carbon (C) turnover. Although deadwood represents an important global C stock, scarce information is available on how slope exposure influences the wood-inhabiting microbiota throughout the decomposition process in an Alpine setting. We therefore evaluated the impact of slope exposure (north-vs. south-facing sites) on physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Topographic features such as slope exposure may have important consequences on deadwood decomposition process 24 and on the underlying soil microbial communities as recently shown in a 2-year mesocosm monitoring of P. abies wood decomposition performed at the same experimental site in the Italian Alps [25][26][27][28] . A faster deadwood decomposition rate at the south-facing slope with respect to the north-facing one was related to a higher bacterial richness and a higher number of detected specialist operational taxonomic units (OTUs) 28 .…”
mentioning
confidence: 86%
“…Topographic features such as slope exposure may have important consequences on deadwood decomposition process 24 and on the underlying soil microbial communities as recently shown in a 2-year mesocosm monitoring of P. abies wood decomposition performed at the same experimental site in the Italian Alps [25][26][27][28] . A faster deadwood decomposition rate at the south-facing slope with respect to the north-facing one was related to a higher bacterial richness and a higher number of detected specialist operational taxonomic units (OTUs) 28 .…”
mentioning
confidence: 86%
“…Several previous studies have revealed the existence of elevational patterns of bacterial community composition (Singh et al ., ; Wang et al ., ; Shen et al ., ), functional gene abundance (Bardelli et al ., ) and functional gene composition (Yang et al ., ). Along with the elevational gradient, we detected shifts in many environmental variables that may influence the bacterial phylogenetic turnover including habitat variables, such as MAT, SOM and pH, and biotic variables, such as the relative abundance of Proteobacteria and Actinobacteria .…”
Section: Discussionmentioning
confidence: 97%
“…Slope exposure was shown to affect not only the soil weathering and biogeochemical processes [24][25][26], but also the composition and activity of soil microbial communities [27][28][29][30][31] and soil fauna [27,32] in mountain forest soils. To date, most of our understanding about the functioning of this type of ecosystems has focused on the bulk soil.…”
Section: Introductionmentioning
confidence: 99%